Gendered perspective on water security, rights and conflicts in sub-Saharan Africa: a systematic review - Mutanda, Gideon Walter; Nhamo, Godwell (Frontiers in Water, 2024)
The 2017 Global Risk Report ranked water crisis third among the top six global risks that greatly impact society. While the water crisis is disproportionately distributed worldwide, sub-Saharan Africa (SSA) has more people (most of whom are women) who face water problems compared to other regions worldwide. Through the application of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol version 2020, a systematic review examining the connection between gender and water security, rights, and water conflicts in SSA was done. A total of 24 out of 229 articles made it into the final analysis. Previous research studies on gender politics in the water sector have done so in a fragmented way, focusing on specific water security parameters. The emerging findings show that 14 years after the adoption of an enforceable human right to water and about 6 years prior to the cut-off date for the 2030 Agenda for Sustainable Development, matters of gender and water in SSA are far from being addressed. Rural people, especially women, still face multiple water-related challenges and conflicts, including discriminatory practices upholding male hegemony in water governance. It is recommended that actors in the water sector precede the implementation of water projects by understanding contextual settings that influence gendered water security. Furthermore, the implementation of the water Sustainable Development Goal (SGD 6) should be done in the context of SDG 5 (Gender Equity) and the prioritization of procedural water justice and governance, access to technical skills, and water conveyance technologies.Systematic review registrationhttps://www.prisma-statement.org/.